1999
DOI: 10.1001/archopht.117.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Oral Acyclovir After Penetrating Keratoplasty for Herpes Simplex Keratitis

Abstract: To determine the efficacy of systemic acyclovir in decreasing complications and improving the outcome of penetrating keratoplasty for herpes simplex virus (HSV) keratitis. Methods: Retrospective study of 53 primary penetrating keratoplasties for HSV keratitis at an eye hospital from January 1, 1989, through December 31, 1996. Medical records were analyzed for history of HSV keratitis, preoperative neovascularization, and disease activity. Postoperative use of acyclovir, recurrence of HSV keratitis, rejection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 29 publications
2
23
0
5
Order By: Relevance
“…Generally, this test might be useful in patients with the consequence of prolonged anti-viral therapy who requires a clear diagnosis before deciding on a specific treatment, for instance, corneal allograft recipients [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, this test might be useful in patients with the consequence of prolonged anti-viral therapy who requires a clear diagnosis before deciding on a specific treatment, for instance, corneal allograft recipients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Because individuals with previous stromal keratitis are at high risk to develop more severe disease, prophylaxis is a substantial means to reduce the personal, social, and financial burdens [15]. A randomized, placebo-controlled clinical trial demonstrated a significantly reduced recurrence rate following twice daily oral acyclovir during a 1-year observation period [11]; long-term acyclovir therapy is known to significantly improve graft outcomes [27] and prevent viral recurrences [29]. Early diagnosis of HSV keratitis is also important in corneal allograft recipients, and HSV keratitis has been described in patients with no history of herpes disease [4,23].…”
Section: Introductionmentioning
confidence: 99%
“…The potential benefits include higher plasma levels of the drug and reduced frequency of administration, although in practice the actual dosage and frequency of antiviral medication required remains uncertain. Treatment with acyclovir 400 mg twice daily for at least 1 year postoperatively has been previously recommended 6,8,13 but longer treatment may be indicated. Conversely, Jansen et al 14 have reported follow-up data for patients given only 6 months postoperative oral acyclovir following PK for HSV keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Patienten mit erhöhtem Risiko für ein erneutes Auftreten einer Herpes-simplex-Keratitis ist eine Dosierung von 800-1000 mg täglich für 6-12 Monate erforderlich [35,36]. In Fällen mit hohem Risiko für eine immunvermittelte Abstoßung und wiederkehrende Herpes-Keratitis ist zusätzlich Mycophenolat-Mofetil (MMF) 2 × 1 g täglich für 6-12 Monate zu verabreichen [37].…”
Section: Postoperatives Management Der Hochrisikokeratoplastikunclassified